Determinants of wage (dis-)satisfaction: Trade exposure, export-led growth, and the irrelevance of bargaining structure - Lucio Baccaro; Erik Neimanns (Max Planck Institute for the Study of Societies, 2021)
Although the determinants of wage militancy and moderation have been studied extensively by comparative political economists, so far the literature has focused on the macro level of analysis. As a result, there has been no attempt to analyze the determinants of individual-level attitudes towards wages. Based on two waves of the International Social Survey Programme, in this paper we fill this gap. We examine to what extent workers internalize the imperatives of competitiveness, and whether wage bargaining institutions facilitate this internalization, as suggested by a large literature on neocorporatism. Surprisingly, we find that the structure of wage bargaining (more or less coordinated or centralized) has no relationship with wage satisfaction or dissatisfaction at the individual level. Instead, wage dissatisfaction decreases strongly when workers are individually exposed to trade and countries rely heavily on export-led growth. Our results point to the need to rethink the determinants of wage moderation. – – In der Vergleichenden Politischen Ökonomie wurden die Bestimmungsfaktoren von Lohnzurückhaltung und Arbeitskämpfen für die Durchsetzung von Lohnforderungen umfassend untersucht. Diese Forschung bewegte sich jedoch bislang auf der Makroebene, sodass es keine Versuche gab, Einstellungen zu Löhnen auf der individuellen Ebene zu untersuchen. Unter Verwendung von zwei Erhebungen des International Social Survey Programme adressieren wir in diesem Beitrag diese bestehende Forschungslücke. Wir untersuchen, in welchem Maße Arbeitnehmende die Erfordernisse von internationaler Wettbewerbsfähigkeit internalisieren und ob, wie die umfassende neokorporatistische Forschung suggeriert, stärker koordinierte und zentralisierte Institutionen von Lohnverhandlungen diese Internalisierung befördern. Überraschenderweise zeigen sich keine Zusammenhänge zwischen der Struktur der Lohnverhandlungen und individueller Lohnzufriedenheit und -unzufriedenheit. Stattdessen zeigt sich jedoch eine geringe Unzufriedenheit mit dem eigenen Lohn, wenn die eigene Beschäftigung vom Außenhandel abhängt und wenn Exporte ein starker Wachstumstreiber des jeweiligen Landes sind. Unsere Ergebnisse weisen auf die Notwendigkeit hin, die Bestimmungsfaktoren von Lohnzurückhaltung neu zu überdenken.
hdl:21.11116/0000-0008-9C46-A
Keywords: 300; collective bargaining; export-led growth; trade exposure; wage moderation; wage preferences; exportgetriebenes Wachstum; internationaler Handel; kollektive Lohnverhandlungen; Lohnpräferenzen; Lohnzurückhaltung